Pengaruh Brand Awareness, Harga Dan Promosi Media Sosial Melalui Instagram Terhadap Keputusan Pembelian Jilbab UmamaDengan Religiusitas Sebagai Variabel Moderating (Studi Kasus : Mahasiswa UIN Sjech M.Djamil Djambek Bukittinggi) - Effendy, Yolanda; Asyari, Asyari (LPPM Institut Pendidikan Nusantara Global, 2024)
The purpose of the study is to analyze the influence of Brand Awareness, Price and Social Media Promotion on purchase decisions, and to estimate religiosity to moderate the relationship between Brand Awareness, Price and Social Media Promotion on the purchase decision of Umama Hijab in UIN Sjech M.Djamil Djambek Bukittinggi Students.The research method uses a quantitative method with Correlation Research.the number of samples was 210 students of UIN Sjech M.Djamil Djambek Bukittinggi. The sampling technique uses Purposive sampling. The data analysis used in this study is the Warp Partial Least Square program with the help of Warppls 7.0 software.The results of the study showed that Brand Awareness was Positive and Significant towards Purchase Decision with a β value of 0.51 and a P-Value of 0.01 small from 0.05 with a contribution by an R2 value of 0.26 which means that the contribution of Brand Awareness to the decision was 26%. Price has a positive and significant effect on the Purchase Decision with a β value of 0.43 and a P-Value of 0.01 less than 0.05 with a contribution by an R2 value of 0.19 which means that the contribution of Price to the purchase decision is 19%. Social media promotion has a positive and significant effect on Purchase Decisions with a β value of 0.53 and a P-Value of 0.01 less than 0.05 with a contribution by an R2 value of 0.28 which means that the contribution of Social Media Promotion to the purchase decision is 28%. Religiosity was able to moderate the influence of Brand Awareness on Purchase Decisions with a moderation effect coefficient of 0.16 and a value and P-Value of 0.01 less than 0.05 with a moderation effect contribution shown by an R2 value of 0.28 (28%). Religiosity moderated the influence of Price on Purchase Decisions with a moderation effect coefficient of 0.20 and a value and P-Value of 0.01 less than 0.05 with a contribution to the moderation effect shown by the R2 value of 0.22 (22%).Religiosity moderated the influence of Social Media Preferences on Purchase Decisions with a moderation effect coefficient of 0.19 and a value and P-Value of 0.01 less than 0.05 with a moderation effect contribution shown by an R2 value of 0.31 (31%).